Complex dayside particle precipitation observed during the passage of a solar wind rotational discontinuity - Wing, Simon; Berchem, Jean; Escoubet, C. Philippe; Farrugia, Charles (Frontiers in Astronomy and Space Sciences, 2024)
The dayside particle precipitation during the passage of a solar wind rotational discontinuity (RD) event on April 10, 2015 is examined and reviewed. The RD leads to complex structures at the magnetopause, boundary layer, mantle, and cusp even though the geomagnetic activity level remains low. Particle precipitation data from DMSP F17 reveal the formation of an unusual boundary layer where the low energy (cold) ions exhibit energy-latitude dispersion that is usually associated with mantle while the high energy (hot) ions look like typical magnetospheric ions. DMSP F17 and F19 observe a double cusp that is a signature of magnetic reconnection occurring at both high-and low-latitudes due to the dominant IMF By. A global MHD simulation of the event supports the existence of the simultaneous reconnections at high-and low-latitude magnetopause that are consistent with the anti-parallel and component merging models, respectively. Finally, Cluster C2, located at high-latitude and high-altitude in the southern hemisphere, observes velocity fluctuations and reversals with peak-to-peak amplitudes >800 km s -1 as it crosses the magnetopause. Guided by the MHD simulation, the Cluster observation can be interpreted as the spacecraft crossing reconnection outflows while moving from one side of the X-line to the other.